PEMETAAN SURABAYA HERITAGE DENGAN GEOGRAPHIC INFORMATION SYSTEM - Evan J Tanjaya; Silvia Rostianingsih; Andreas Handojo (Jurnal Infra, 2016)
Heritage is a word derived from the English language that has heritage or legacy significance. There are a lot of heritage that is owned by the city of Surabaya, one of which is a relic of historic sites and heritage buildings. Remains of historic sites and heritage buildings in Surabaya consist of shopping malls, museums, monuments, hospitals and graves has a history behind it. But not many people who know the location of the existing heritage. Therefore, made the application of GIS (Geographic Information System) based web.The application consists of the three main menu main page, user and admin, on the main page, and users can view detailed information about the location selected by the user such as a photo location, history and opening hours and admission price. On the user page, users who have registered can apply for a new location and a new category to the administrator. And on page administrator, admin can add or change the location information.Overall, the web has been able to run well, capable of displaying location information required by the user.